Trends and Implications of Ribosome-associated Protein Quality Control in Diseases: A Bibliographic Analysis - Chen, Leijie; Song, Wanjuan; Qing, Yumin; Tan, Yuyong; Liu, Jia; Lv, Liang (Current Medicinal Chemistry, 2025)
ObjectiveRibosome-associated protein Quality Control (RQC), comprising several well-organized processes and crucial factors, provides translational surveillance in cells by recognizing and degrading aberrant nascent proteins arising from ribosome stalling. Although rapid progress has been made in RQC, a bibliographic analysis of RQC-related literature studies for the overall trends and research progress, particularly the correlation of RQC with diseases, is absent.MethodsWe obtained scientific outputs of global RQC between 1999 and 2022 by Web of Science Core Collection (WoSCC). CiteSpace, VOSviewer, and a package of R called bibliometrix were applied to explore the current research status, hotspots, and the relationship between RQC and diseases.ResultsA total of 429 articles have been included in this study, and the number of published studies increases annually. The United States and Germany have been found to lead in this field. An analysis of the keywords has shown “initiation”, “aggregation”, “structure basis”, “elongation”, and “degradation” to be the emerging themes of RQC. Keywords co-occurrence has shown E3 ubiquitin ligase to bridge RQC and neurodegeneration.ConclusionThrough a summary of the current studies on RQC, our study has provided evolutionary trends and frontiers in this field by mathematical analysis and visualization, implying the potential of RQC in neurodegeneration and other diseases.
Keywords: ribosome collision